Theater in the Spanish school of Rabat (Journal of Parents and Teachers, 2014)
The theater is an artistic manifestation that allows to work with strategies of socialization, of resolution of conflicts, and of communication from a playful, pedagogic and motivational approach. The authors of the article show the capacity of education that the performing arts have, providing examples of works of didactic interest.
Keywords: Theater; communication strategies; playful approach; didactic resource; motivation.